Using of actual author's project technology "Fashion-constructor" for preparing specialists in the direction of "Fashion design" - Andreeva V. V. (Pedagogical excellence and pedagogical technologies, 2020)
the article deals with the development and use of new educational technologies for the training of fashion designers. The article describes the innovative author's development of training in clothing design. The advantage of this method for motivation and formation of professional competencies is proved. As well as creating a high-quality educational environment directed at developing the creative abilities of students and their motivation to apply the results in practical project activities.
Keywords: образовательный процесс; проект; мода; творческий процесс; educational process; creative process; project; дизайн одежды; fashion; проектирование одежды; инновационные образовательные технологи; конструктор одежды; ассортимент одежды; коллекция одежды; новые идеи; fashion design; clothing design; innovative educational technologies; clothing designer; clothing range; clothing collection; new ideas